PENGEMBANGAN EKONOMI HIJAU MELALUI PEMBERDAYAAN MASYARAKAT MELALUI SEKTOR PERKEBUNAN DI DESA SELELOS - Insani, Nafaza Nur; Jannah, Alya Raudhatul; fahir, Muhammad; Wulansari, Arum; Rahmah, Fadila Ulya; Nazah, Gebrilla Niftita; Wiradharma, I Gde Putu Vigneswara Angga; Ardiansyah, Lalu Muhammad Ari; Chair, Salma; Salsabila, Violeta Karin (Universitas Mataram, 2024)
Real Work Lectures (KKN) are a form of student service to the community as part of the third